Regional variation in overweight and associations with regional profiles using a Japanese national open-source database - Megumi Yoshigai; Etsu Goto; Daisuke Takada; Yuichi Imanaka (PLoS ONE, 2025)
The objectives of this study were to describe regional variation in overweight and to investigate factors associated with overweight at the secondary medical area (SMA) level, accounting for regional economic sector profiles. We utilized data from the specific health checkup, which targets individuals aged 40–74 years. Following descriptive analyses, we employed partial least squares regression analyses using an open-access version of specific health checkup data from the National Database of Health Insurance Claims and Specific Health Checkups of Japan. This approach allowed us to identify latent variables related to regional variation in overweight and to examine associated lifestyle and socioenvironmental factors. Identifying these latent variables helps uncover underlying regional or socioeconomic patterns not directly observable, thereby informing more targeted public health interventions. The distinct characteristics of areas associated with a higher proportion of overweight persons were identified—the key latent variable encompassing low socioeconomic status and a high proportion of family workers. Additionally, our findings suggested that the drinking and eating environment may present challenges in regions with a high proportion of workers in the information and real estate sectors. In contrast, reduced walkability of the environment may be problematic in regions with many workers in the manufacturing and transportation sectors. Our study underscores the importance of addressing the unique challenges faced by each area with attention given to their local traits and industrial structures, which may have unconsciously shaped residents’ lifestyles and daily behaviors. As area-level variation in overweight and obesity related to contextual factors, such as economic sector profiles, have not been extensively studied internationally, this study provides a valuable insight into research on factors associated with overweight.